Effect of CSR Education on Consumer Ethical Behavior - Chen, Fei Ie (2009)
Corporate Social Responsibility (CSR) is a growing area of interest for Government, corporations, activists and other agents especially with the increased globalization in the world today. Consumers, being the largest group of stakeholders need to be fully informed of the overall CSR concept in order to avoid being manipulated by firms’ action. Smart consumerism firstly needs to identify about the right and wrong doings of firms prior to their decision making process; and this is where the role of CSR education comes in. Many corporations, organizations and educationalist have taken the initiative to encourage the provision of knowledge to consumers; for example by introducing CSR course in formal education system, spreading the news about ethical consumption in media and encouraging consumers to take part in debates relating to ethical buying behaviour.